Associations of geographical space with perinatal mortality: integrative literature review (Research, Society and Development, 2020)
The present study aims to identify evidence in scientific production about the relationship between geographic space and perinatal mortality. It is an integrative literature review study, which followed the methodological assumptions according to Mendes, Silveira, Galvão, carried out from July to December 2019, in the Lilacs and Medline databases. The findings of the present study showed that spatial analysis is used as a tool to identify relationships between geographic space and perinatal mortality. Deaths in perinatality are considered preventable deaths, in addition, studies indicate that the incompleteness of data sources can represent a weakness in establishing the relationship between geographic space and perinatal deaths.